Penerapan Pendekatan CRT Berbantuan Media Genially untuk Meningkatkan Hasil Belajar Siswa Kelas V - Diah Fitriani Maula Ischaq; Nafiah Nafiah; Aris Budianto (STKIP AL HIKMAH SURABAYA, 2022)
The aim of this research is to improve learning outcomes in the Pancasila Education subject with diversity material in Surabaya at SDN Karah 1/411 Surabaya. This classroom action research was carried out collaboratively and carried out in 2 cycles. The research began by conducting a pre-cycle, namely a diagnostic test of students' initial abilities and identifying material diversity that existed in Surabaya. Next, cycle 1 which includes a) planning which includes preparing teaching modules, teaching materials, observation sheets, LKPD and assessments, b) action, c) observation and d) reflection. The researcher reflects on the activities that have been carried out to determine the weaknesses and strengths in cycle 1 which will be used as reference material to formulate problems that will be corrected in cycle II. The research results show that there is an increase in cognitive learning outcomes in color mixing material. In the classical learning results of cycle 1, the percentage was 61.85%. In cycle II there was an increase, namely by obtaining a percentage of 88.15% above the KKM. Based on the research results, cognitive learning outcomes in diversity material in Surabaya with the help of genially media can be stated to have increased.